Cross-Sectional Information on Pore Structure and Element Distribution of Sediment Particles by SEM and EDS. (14th September 2017) - Chen, Minghong; Zhao, Huiming; Fang, Hongwei; Zhang, Yuefeng
Abstract : The interaction between pollutants and sediment particles often occurs on the particle surface, so surface properties directly affect surface reaction. The physical and chemical processes occurring on sediment particle surfaces are microscopic processes and as such need to be studied from a microscopic perspective. In this study, field emission scanning electron microscopy (SEM) and energy dispersive X-ray spectrometer (EDS) were adopted to observe and analyze the pore structure and element distribution of sediment particles. In particular, a special method of sample preparation was used to achieve the corresponding cross-sectional information of sediment particles. Clear images of a particle profile and pore microstructure were obtained by high-resolution SEM, while element distribution maps of sediment particles were obtained by EDS. The results provide an intuitive understanding of the internal microenvironment and external behavior of sediment particles, in addition to revealing a significant role of pore microstructure in the adsorption and desorption of pollutants. Thus, a combination of different experimental instruments and observation methods can provide real images and information on microscopic pore structure and element distribution of sediment particles. These results should help to improve our understanding of sediment dynamics and its environmental effects.